THE CONCEPT OF EDUCATION ACCORDING TO IBNU KHALDUN AND ITS PARALELISM TO INDONESIAN EDUCATION - Natacia Mujahidah; Muhammad Alpin Hascan (Yayasan Hurriah, Banda Aceh, 2023)
Ibn Khaldun was the greatest Muslim scientist of his time. His thoughts on the concept of education can still be used and have a great contribution today. The purpose of this study is expected to shed light on his biographical sketches, his educational thinking, and his parallelism to modern education. This research is included in the type of descriptive qualitative research by explaining the data taken using the library research method (literature) with a socio-historical approach and describing it systematically and factually based on the facts found. Furthermore, the data is then processed and analyzed using source triangulation, primary and secondary books along with taken from several other scientific paper writings. The results showed that Ibn Khaldun's concept of thinking about education is still relevant and feasible to be applied in today's education, it should be applicable by educational institutions. Not only is it devoted to the western world, but the main mecca of Muslims is Islamic figures, one of which is Ibn Khaldun. The concept of education according to Ibn Khaldun's perspective is in line with the goals of national education. One with the other has similarities with the same goal in achieving the learning of students who have faith, character and knowledge.